Strategi Pemasaran Berbasis Ekosistem dalam Pengelolaan Perikanan Tuna: Studi Kasus di Nusa Tenggara Timur - Pua Tingga, Chairul; Geno, Zainal Arifin Pua; Gadi, Dewi Setiyowati (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2025)
Ecosystem-based marketing strategy in tuna fisheries management that focuses on implementing sustainability principles in marketing and managing fisheries resources. This research aims to identify effective strategies for marketing tuna products by considering ecological and social impacts, as well as ensuring the long-term sustainability of fisheries resources. The method used in this research involved analysis of primary and secondary data, which included interviews with key stakeholders in the tuna fishing industry and analysis of related literature. Research findings show that integrating marketing strategies with an ecosystem-based approach can increase the added value of tuna products, expand market access, and support conservation efforts. In conclusion, implementing an ecosystem-based marketing strategy not only supports environmental sustainability but also provides economic benefits for fishing industry players. Therefore, this approach is recommended as a model for developing a more sustainable fishing industry in the future